Appraisal of Transparency International in the Czech Republic - Kubrová, Lucie (2017)
This thesis aims to assess the marketing strategy and HR management done at Transparency International in the Czech Republic and to propose improvements that could help increase the awareness about the organization. To achieve this, the perception of the Czech citizens is evaluated via questionnaire. Afterwards the marketing strategy done in the Czech branch is described based on the interview with the representative of Transparency International. In the end, the individual elements are compared which enables to define improvement recommendations for the organization.